2018
DOI: 10.1055/s-0038-1672199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Intervention to Improve Life-Space Mobility and Self-Efficacy in Patients following Total Knee Arthroplasty

Abstract: Life-space mobility describes the spatial areas through which an individual moves, and the frequency and need for assistance. Although patients with knee osteoarthritis (OA) have shown restricted life-space mobility, total knee arthroplasty (TKA) does not improve it beyond preoperative levels. Life-space mobility after TKA was influenced by self-efficacy for walking tasks; thus, an intervention to improve self-efficacy for walking tasks may contribute to better life-space mobility. We provided a walking event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Similarly, although a resistance and balance training programme decreased falls risk, it did not increase life-space in care home residents [ 29 ]. After knee arthroplasty, patients who were less frail (by selection) and receiving an extended walking intervention showed improved life-space [ 30 ]. However, a multidisciplinary team community rehabilitation intervention demonstrated greater life-space in frail patients, even after 12 months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although a resistance and balance training programme decreased falls risk, it did not increase life-space in care home residents [ 29 ]. After knee arthroplasty, patients who were less frail (by selection) and receiving an extended walking intervention showed improved life-space [ 30 ]. However, a multidisciplinary team community rehabilitation intervention demonstrated greater life-space in frail patients, even after 12 months [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, performing aerobic exercise and strength training for RA patients also leads to improved self-health assessment and reduced support from people around them 19,20) . In addition, it has reported that walking practice through obstacles such as pedestrian crossings, stairs, walking on an unpaved road, and going up and down a slope is helpful in expanding the living space for patients post-TKA 21) . These approaches may lead to the long-term improvement of the patient's health assessment and independence of daily life.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to some participants' goals involved leaving their home and intervention strategies, such as adding handrails to facilitate that goal. Evidence on improving life‐space in older adults using interventions has been limited and mixed 22‐25 . Prior studies show disparities in life‐space restriction by race and sex, with Black women having high restriction 26 .…”
Section: Discussionmentioning
confidence: 99%